Dynamic signature of the thermodynamic transition in a novel mean field system - Anwar, Ehtesham; Nandi, Ujjwal Kumar; Patel, Palak; Kumawat, Sanket; Maitra Bhattacharyya, Sarika (Journal of Chemical Physics, 2025)
Understanding the connection between thermodynamics and dynamics in glass-forming liquids remains a central challenge in condensed matter physics. In this study, we investigate a novel model system that enables a continuous crossover from a standard three dimensional liquid to a fully connected mean field like system by introducing pseudo neighbors. These pseudo neighbors enhance the effective connectivity of the system without altering its local structure. While their presence slows down the dynamics, they influence thermodynamic properties even more significantly. In particular, the configurational entropy obtained via thermodynamic integration vanishes at a temperature much higher than the temperature where the dynamics begin to slow down, leading to a clear breakdown of the Adam-Gibbs relation. To uncover a possible dynamical signature of this thermodynamic transition, we analyze bond breakage dynamics. Unlike real-real bonds, which decay similarly in both the parent Kob-Andersen model and its mean field variant, real-pseudo bonds exhibit long lived, persistent behavior with strong temperature dependence. These bonds do not fully decay over time, leading to a finite saturation value of the bond breakage correlation function. Remarkably, we show that the number of surviving pseudo bonds can be analytically estimated and correlates directly with the thermodynamic transition temperature T-K. We propose a phenomenological relation between T-K and the number of surviving pseudo-bonds, establishing a novel link between thermodynamic and dynamic observables. Our results suggest that these persistent pseudo bonds serve as a robust dynamical signature of the thermodynamic transition, and the system might have properties analogous to those of randomly bonded ultrastable glasses.

Structure-dynamics correlation and its link to fragility and dynamic heterogeneity - Sharma, Mohit; Sastry, Srikanth; Maitra Bhattacharyya, Sarika (Journal of Statistical Mechanics-Theory and Experiment, 2025)
Understanding the connection between structure, dynamics, and fragility, the rate at which the relaxation time grows with the decreasing temperature, is central to unravelling the glass transition. Fragility is often associated with dynamic heterogeneity, implying that if the structure influences the dynamics, more fragile systems should exhibit stronger structure-dynamics correlations. In this study, we test the generality of this assumption using the Lennard-Jones (LJ) and Weeks-Chandler-Andersen systems, where the fragility is tuned via the density, and a modified LJ (q, p) system, where the fragility is varied by changing the potential softness. We define a structural order parameter based on a mean-field caging potential and analyse the energy barriers at both the macroscopic and microscopic levels. While the macroscopic free energy barrier slope correlates with fragility, the microscopic free energy barrier does not show a consistent trend. Instead, it exhibits a strong correlation with a structure-dynamics correlation measure obtained from isoconfigurational ensemble simulations. Interestingly, the two systems showing the highest structure-dynamics correlation, LJ at rho = 1.1 and the (8, 5) model, are respectively the least and most fragile within their classes. These systems exhibit broad mobility distributions and large non-Gaussian parameters but low four-point susceptibilities, suggesting a decoupling between the spatial correlation length and mobility contrast. Both systems lie in the enthalpy-dominated regime and are close to the spinodal, pointing to mechanical instability as a source of heterogeneity. Our results reveal that the structure-dynamics correlation is more closely linked to the contrast in individual particle mobility than to the spatial extent of dynamic correlations that typically scale with fragility.
Keywords: dynamical heterogeneities; Glasses; glassy dynamics; slow relaxation; structural